2016
DOI: 10.1016/j.exger.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

What physical performance measures predict incident cognitive decline among intact older adults? A 4.4year follow up study

Abstract: Reductions in physical performance, cognitive impairment (CI) and decline (CD), are common in older age, but few prospective cohort studies have considered the relationship between these domains. In this study we investigated whether reduced physical performance and low handgrip/lower limbs strength, could predict a higher incidence of CI/CD during a 4-year follow-up among a cohort of elderly individuals. From 3099 older community-dwelling individuals initially enrolled in the Progetto Veneto Anziani (PRO.V.A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
94
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 81 publications
(108 citation statements)
references
References 47 publications
(40 reference statements)
6
94
1
7
Order By: Relevance
“…However, when considering the ROC curve for handgrip strength, the data suggested this is not strongly associated with depression, reinforcing the concept that SPPB is probably the best test in predicting depression at the follow-up. When one considers that SPPB also appears to be useful in predicting cognitive decline 14 and mortality 16 , routine screening of physical performance in clinical practice is warranted.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, when considering the ROC curve for handgrip strength, the data suggested this is not strongly associated with depression, reinforcing the concept that SPPB is probably the best test in predicting depression at the follow-up. When one considers that SPPB also appears to be useful in predicting cognitive decline 14 and mortality 16 , routine screening of physical performance in clinical practice is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…18 In addition to a paucity of data, there is an absence of studies comparing the prognostic ability of the different physical performance and muscle strength tests in predicting depression in older adults. Understanding such information is important and valuable for clinicians to identify those most at risks and previous research considering objective physical performance and future mortality 16 and poor cognitive status, 14 have demonstrated that not all tests have the same predictive power. 16 Given the aforementioned limitations and gaps in the literature, the aim of the present study was thus to examine which objective physical performance measures provide an optimal predictor of incident depression in a representative cohort of older subjects over 4 years of follow-up.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations